Frame Alignment Between Environmentalists and the Sámi in the Forest Dispute in Inari, Finland Until the 2000s—Competing Conservation Needs and Obstacles for Co-Living With the Non-Human - Nyyssönen, Jukka (Frontiers in Conservation Science, 2022)
The cooperation between Sámi actors and environmentalists in the resistance of loggings in the conflict over forestry in Inari, in Finnish Sápmi, between 2003-2006 has been presented as cohesive alliance, innovative in creating new political space and channels of influence. In closer look, there were foundational non-aligning factors causing friction to the alliance, relating to the legitimate place of the non-human in the biotic system. I shall examine to what extent and why the frames employed aligned or conflicted. One way to grasp the fragility of the frame alignment is to study the opinions held by the different actors on what needs restoring/conserving, whether these are economic, ecological or cultural elements, or a combination of these, and how the entities to be protected were situated in time. The historical context of this article is the long series of forestry conflicts in Inari, against which the transformations of environmental, herder and forestry frames are studied. It is argued that the combination and amount of the non-human animals to be protected was one root cause for dis-alignment, deepening the rifts between environmentalists and the Sámi to this day.